Arab Nationalism in Palestine in the Beginning of the 20th Century - L. M. Samarskaia (MGIMO University Press, 2019)
The article is dedicated to the emergence of the Arab national movement at the beginning of the 20th century. This topic is still relevant in our days since revealing the origins of political and social processes in the Middle East of the 21st century is necessary for their understanding. The main issues which are considered by the author are the following: which factors had crucial influence on the emergence of Arab nationalism (panarabism as well as regionalism), when exactly it was formed and what were the specifics of its emergence in Palestine.The author defines three main periods in the genesis and formation of the Arab national movement at the beginning of the 20th century. The first is the Nahda, the Arab cultural revival of the second half of the 19th century, which became a foundation for the later development of nationalist ideas. However, the author tries to show that the cultural revival itself was not nationalistic. The second key period is the political expression of the Arab national movement in the first decades of the 20th century, with the ottomanist and later pan-Turkist policy of the Ottoman government having the decisive influence. This policy was nationalist in essence. Zionism, as noted in the text, was not such an important issue for the nascent pan-Arab movement before the First World War, although it caused concern among the locals in Palestine. The third key stage, that was decisive in the Arab national development, is the Great Arab Revolt, which, despite the fact that it was not massive and universal, forced the pan-Arab movement enter the international arena for it attracted the attention of the great powers – mainly with the help of McMahon–Hussein correspondence. In result, during the postwar settlement, pan-Arabism became more popular and internationally recognised phenomenon, although eventually it happened to be divided into a multitude of regional movements, in particular – Palestinian nationalism fostered by the Anglo-French division of influence zones in the Middle East.In general, the formation of the Arab national movement was a multidimensional and gradual phenomenon influenced by a variety of factors. At the same time, the emergence of the regional groups had its own specifics; originally belonging to the Pan-Arab movement, although with their own features, after the First World War these groups became largely independent.